2005
DOI: 10.1021/nl050928v
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering from Individual Au Nanoparticles and Nanoparticle Dimer Substrates

Abstract: Surface-enhanced Raman scattering (SERS) intensities for individual Au nanospheres, nanoshells, and nanosphere and nanoshell dimers coated with nonresonant molecules are measured, where the precise nanoscale geometry of each monomer and dimer is identified through in situ atomic force microscopy. The observed intensities correlate with the integrated quartic local electromagnetic field calculated for each specific nanostructure geometry. In this study, we find that suitably fabricated nanoshells can provide SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
917
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,089 publications
(950 citation statements)
references
References 41 publications
27
917
3
3
Order By: Relevance
“…With these parameters, we find that a photonic band gap appears between frequencies 0.8225 and 0.9843 eV. Note that the lower edge of the band gap lies near ω x sp and the QD transition frequencies ω 12 and ω 13 . The vacuum decay rates for the QD are taken as 0 2 = 0 3 = 0.2 μeV, and in the presence of the photonic crystal it is found that 21 = 1.1370 μeV and 31 = 1.1127 μeV.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…With these parameters, we find that a photonic band gap appears between frequencies 0.8225 and 0.9843 eV. Note that the lower edge of the band gap lies near ω x sp and the QD transition frequencies ω 12 and ω 13 . The vacuum decay rates for the QD are taken as 0 2 = 0 3 = 0.2 μeV, and in the presence of the photonic crystal it is found that 21 = 1.1370 μeV and 31 = 1.1127 μeV.…”
Section: Resultsmentioning
confidence: 77%
“…They arise due to the dielectric contrast between graphene and the surrounding dielectric medium. Plasmonics is widely studied due to applications in ultrasensitive optical biosensing, 13 photonic metamaterials, 14 light harvesting, 15 optical nanoantennas, 16 and quantum information processing. 17 Generally, noble metals are considered as the best available materials for the study of surface plasmon polaritons.…”
Section: Introductionmentioning
confidence: 99%
“…The electromagnetic (EM) enhancement near the metal surface, which is caused by the resonant excitation of surface plasmon [5], is the dominating reason for the surface-enhanced Raman scattering (SERS) [1,6]. Huge SERS with single molecule sensitivity can be obtained when molecules are located in the nano-gap between two metallic nano-structures [1,2,7,8,9]. A lot of efforts have been made to seek extreme sensitive SERS substrates [10,11,12].…”
mentioning
confidence: 99%
“…Often, a further simplified formula is used (as in [30]) that expresses the Raman enhancement as the product of the local intensity enhancement factors at the excitation and Raman-shifted frequencies at the position of the Raman-emitting molecule. As we noted in the Introduction, proposed in [9], this formula is given by (1).…”
Section: Sers Enhancement Factor In Green's Function Theorymentioning
confidence: 99%